Cyprus : Report on the Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report, 2005)
This Report on the Observance of Standards and Codes (ROSC) examines Fiscal Transparency for Cyprus. The report reveals that Cyprus has been making major progress in improving fiscal transparency, helped by the government's efforts to strengthen budget management systems and comply with the European Union acquis communautaire. As a result, the country now fully meets or even exceeds the code's standards in many areas. The momentum of fiscal management reform efforts should be maintained to meet the requirements of the code in additional areas.